The Effects of Parental Conflicts and Divorce Towards Self-efficacy in Romantic Relationships of Young Adults Male - Aulia Rahma, Fadilla M.; Dwi Hastuti; Herien Puspitawati (Open Access Indonesia Journal of Social Sciences, 2023)
Parental conflict and divorce trends have been increasing over the years and hinder parents from nurturing their children, particularly fathers. Fathers are more likely to disengage in parenting after a divorce. This may affect children in their romantic relationships in later life. This study aimed to examine the effects of parental conflict and divorce and father parenting practices towards self-efficacy in romantic relationships of young adults male. The study applied quantitative methods with correlational, comparative, and regression analysis. 62 male and single young adults whose parents were divorced before the age of 18 were involved and chosen with purposive sampling. The data was collected by using the children's perception of interparental conflict scale (α=0.92), parental acceptance-rejection questionnaire (α=0.86), and self-efficacy in romantic relationship scale (α=0.89). The results revealed that there is a partial correlation between parental conflict intensity and relationship anxiety and other aspects related to the self-efficacy of young male adults. Paired t-test illustrated differences in self-efficacy in romantic relationships based on individual characteristics and father parenting practices (negative). Regression analysis also demonstrated a significant effect of father parenting practices, both positive and negative, towards self-efficacy in romantic relationships. In conclusion, the efficacy of romantic relationships in early adulthood from divorced families is influenced by negative paternal parenting.